Fifteen years since the presentation of the first Dean's Awards for scientific research by students at the Faculty of Medicine of the University of Maribor - Pahor, Dušica (Acta Medico-Biotechnica, 2023)
In 2007, the management of the Faculty of Medicine at the University of Maribor (the MF UM), concluded that scientific research by students must be encouraged after a proposal was received by the vice dean for research. Consequently, the Dean's Awards were introduced for the best students in the field of research at the MF UM. The aim was to help our students gain necessary research experience and to enable evaluation of their research during their studies. Our students’ research papers are also eligible for Perlach’s Award at the UM, which is presented annually to the UM students with the best research papers in various fields of study.The first Dean's Awards were presented 15 years ago on December 1, 2008, on the day of the establishment of the MF UM. Since then, the awards have been presented each year. Since 2010, in addition to the Dean's Awards, Dean's Acknowledgements have been presented for research of high quality that was not shortlisted for awards. Awards and acknowledgements are presented each year by the dean and vice dean for research activity at the MF UM on the day of the establishment of the faculty. After the presentation of the Dean's Awards, a short biography of the prize winner and research is reported with a short introduction.